Asuhan Kebidanan Berkelanjutan (Continuity of Care) pada Ny. N di Puskesmas Banjardawa Kabupaten Pemalang : Penelitian - Tyastuti Gitasari; Uun Wanisah; Tri Yulianti; Fitria Hikmatul Ulya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are important indicators of a country's health. The target for reducing MMR in 2024 is 183 per 100,000 live births, and IMR is 16 per 1,000 live births (Ministry of Health, 2024). To achieve optimal health, the role of midwives is very important in detecting complications during pregnancy, childbirth, postpartum, and newborn care. This study aims to describe the implementation of Continuity of Care for Mrs. N at the Banjardawa Community Health Center, Pemalang, by implementing Varney's 7 steps and SOAP documentation from pregnancy to newborn. The research method uses a qualitative case study with midwifery management based on Varney's 7 steps. The study was conducted at the Banjardawa Community Health Center, Pemalang Regency, on October 17, 2024–June 14, 2025, with Mrs. N, 25 years old, as the subject. Data were collected through interviews, observations, and documentation studies (medical records, KIA books, ultrasound results, and partographs). The results showed that the midwives carried out all stages of midwifery care according to procedures, from assessment to evaluation during pregnancy, labor, postpartum, and newborn care. Ms. N's ongoing midwifery care went smoothly without any danger signs or complications.